ANALISIS SIFAT HIDROFOBIK PERMUKAAN HDPE BERDASARKAN NILAI TOTAL HARMONIC DISTORTION - Abdul Syakur; Hermawan Hermawan; Sarjiya Sarjiya; Hamzah Berahim (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2009)
Polymer material has been developed to replace the porcelain insulator material and glass. When it is used as outdoor insulator, environmental conditions have a significant influence to the value of surface discharge current, especially for the coastal area and industry. Salt, dust and chemicals contaminant are suspected as the causes of initial current of surface discharge and the insulator surface degradation which lead to a flashover. To analyze the performance of the insulator surface when the leakage current occurs, the Total Harmonic Distortion (THD) is needed to be determined. The value of THD leakage current indicates the hydrophobic characteristic of surface material. This paper analyzes the results of leakage current measurement in laboratory-scale based on IEC 587:1986 with Inclined-Plane Tracking (IPT) method to the High Density Polyethylene (HDPE) polymer material which is provided in smooth and rough surface. The testing voltage is 50 Hz AC. Data of leakage current magnitude values cover its maximum average as a function of time and the result of FFT to the wave form of the leakage current. As the result, the value of percentage THD decrease as the function of time. The smooth surface material has THD value 43.42% and the rough surface has 15.89%.